EFFECT OF CARDIOVASCULAR DRUGS ON BONE HEALTH AND THE POSSIBILITY OF THEIR USE FOR THE PREVENTION OF OSTEOPOROSIS - I. A. Skripnikova; K. E. Sobchenko; O, V. Kosmatova; D. V. Nebieridze (Столичная издательская компания, 2015)
Widespread use of antihypertensive and lipid-lowering agents in clinical practice determines the necessity of knowledge of their pleiotropic effects. Results of studies of the effect of cardiac drugs and, first of all beta-blockers, ACE inhibitors, diuretics, and statins on bone are presented. Mode of action on the bone mineral density , markers of bone turnover and ultimately impact on the incidence of fractures associated with osteoporosis are discussed. At the present time there are no sufficient evidences of positive effect of these medications on bone coming from randomized controlled trials. It is not possible to recommend discussed cardiovascular drugs for prevention of osteoporosis and fractures, as well as registration new indications for them. However , knowledge of additional effects on the bone metabolism in cardiovascular drugs, will allow doctors to choose optimal treatment of hypertension and lipid disorders, taking into account the state of bone tissue. At the same time it will also allow to prevent osteoporosis in patients having osteoporosis risk factors or initial signs of bone loss.